List of Members, Associates and Junior Associates Geographically Arranged (681bdd36-3183-46ef-be15-2d4b775221d2) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
ALABAMA Altoona -Cain, J Anniston-Cowie, L K Hermrod, A A White, H E Bessemer -Abbott, C E Ball, E M Mitchell, F R Thompson, N E Birmingham -Adler, J E Aldrich, T H Aldrich, T H, Jr Blackburn, A R Bush, M W Clark, G H Cowrn, P G Crane, W R Crawford, G G Crockard. F H